2013
DOI: 10.1186/1471-2466-13-37
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ghrelin Treatment on Exercise Capacity in Underweight COPD Patients: a substudy of a multicenter, randomized, double-blind, placebo-controlled trial of ghrelin treatment

Abstract: BackgroundThe aim of this substudy of the ghrelin treatment, multicenter, randomized, double-blind, placebo-controlled trial was to investigate the effects of ghrelin administration on exercise capacity and the underlying mechanisms in underweight patients with chronic obstructive pulmonary disease (COPD) using cardiopulmonary exercise testing.MethodsTwenty underweight COPD patients were randomized to pulmonary rehabilitation with intravenous ghrelin (2 μg/kg, n = 10) or placebo (n = 10) twice daily for 3 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
3
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 32 publications
2
27
3
1
Order By: Relevance
“…The substudy showed that ghrelin administration improved exercise capacity and ventilatory cardiac data, but that endurance time was not increased after administration of ghrelin; in other words, COPD patients treated with ghrelin could exercise more rapidly. Absolute dyspnea level during exercise was not significantly improved compared with placebo [21], however, which suggests a discrepancy between improved physiological findings and measures of direct patient benefit, i.e., exertional dyspnea level. Therefore, after completion of the main multicenter trial, including the substudy, to clarify more precisely the exertional dyspnea pattern after treatment with ghrelin, we examined, for a subpopulation of the substudy (n = 20), whether ghrelin administration affects the break-point in dyspnea during exercise.…”
Section: Introductioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The substudy showed that ghrelin administration improved exercise capacity and ventilatory cardiac data, but that endurance time was not increased after administration of ghrelin; in other words, COPD patients treated with ghrelin could exercise more rapidly. Absolute dyspnea level during exercise was not significantly improved compared with placebo [21], however, which suggests a discrepancy between improved physiological findings and measures of direct patient benefit, i.e., exertional dyspnea level. Therefore, after completion of the main multicenter trial, including the substudy, to clarify more precisely the exertional dyspnea pattern after treatment with ghrelin, we examined, for a subpopulation of the substudy (n = 20), whether ghrelin administration affects the break-point in dyspnea during exercise.…”
Section: Introductioncontrasting
confidence: 61%
“…These encouraging results prompted us to undertake a multicenter, randomized, double-blind, placebo-controlled trial of ghrelin with 33 COPD patients; this showed that ghrelin administration improved symptoms and respiratory muscle strength [20]. In parallel with the main multicenter trial, to understand the precise mechanism that underlies the improvement of exercise performance or symptoms, a substudy with 20 COPD patients was conducted in a single center (Toneyama National Hospital) as part of the main multicenter trial [21]. The substudy showed that ghrelin administration improved exercise capacity and ventilatory cardiac data, but that endurance time was not increased after administration of ghrelin; in other words, COPD patients treated with ghrelin could exercise more rapidly.…”
Section: Introductionmentioning
confidence: 98%
“…However, there was no effect of nitric oxide inhalation [95]. A study of ghrelin in underweight COPD patients showed an average reduction in V′E-V′CO 2 slope of ∼4 units [96]. In cystic fibrosis, oxygen therapy reduced the minimum V′E-V′CO 2 [58].…”
Section: Clinically Meaningful Differencementioning
confidence: 99%
“…One clinical trial with ghrelin analogues have been conducted in COPD patients. They reported improvements of ventilatory efficiency at peak exercise, reflected by increased peak oxygen uptake 236. However, it did not translate in improved 6‐min walk distance, and no data are available about body composition or food intake.…”
Section: Compromised Dietary Intakementioning
confidence: 98%